THE RELATIONSHIP OF PRICE PERCEPTION AND ATTRACTION OF ONLINESHOP ADVERTISEMENT WITH INTEREST IN BUYING THROUGH SOCIAL MEDIA POST-COVID-19 PANDEMIC - Usman Effendi; Agnesia Amelia; Gunawan; Muhammad Usman; Radhiana (Jurnal Sociohumaniora Kodepena (JSK), 2022)
Buying interest in marketing is an interesting thing to know. Moreover, related to the perception of price and the attractiveness of advertising through social media. This study aims to determine the relationship between price perceptions and the attractiveness of online shop advertisements with interest in buying fashion products through social media after the COVID-19 pandemic.. The problem is whether there is an onlineshop ad attraction relationship with the interest of buying fashion products through social media. Subjects in this study were students who have done fashion onlineshopping through social media as much as 186 students using incidental sampling. The instruments used in this study consisted of price perceptions, the attractiveness of onlineshop advertisements, and buying interest. The research was conducted with quantitative approach and using multiple linear regression analysis technique. The result of analysis shows that there is relation between perception of price and attractiveness of onlineshop advertisement with buying interest of fashion product through social media with correlation coefficient R = 0,554, F = 40,532 and p = 0,000 (p <0,05). The analysis proves that the perception of price and attractiveness of onlineshop advertisement have adjusted R square equal to 30,7% with buying interest and the rest equal to 69,3% contributed by other variable not examined in this research.